Effectiveness of Silica Sulphate Catalyst Based on Rice Husk Ash in The Oleic Acid Esterification Process - Lidya Elizabeth; Ade Rifqi Maulana; Anisa Dwi Febriani; Saripudin; Eko Andrijanto (Fluida, 2024)
Rice husk contains a lot of silica, so it is widely used as research material. One example is as a raw material for the synthesis of silica sulfate. Silica sulfate was synthesized using the sol-gel method with an impregnation time of 6 hours and 2 hours of calcination with variations in calcination temperature of 400-800oC. The analysis carried out on the silica sulfate catalyst is the analysis of acid concentration and FTIR. The best acid concentration results were 0.86 mmol/gram at 400oC. Characterization with FTIR showed similar peaks between silica and silica sulfate. The -OH and Si-O groups appeared at the peak of the analysis results, indicating that the synthesis of silica from rice husk had been carried out successfully. Modifying silica with sulfuric acid is not obvious through FTIR because the S-OH groups of sulfate ions overlap with the silica atoms in siloxane. The resulting silica sulfate is used as a catalyst in the esterification reaction of oleic acid with methanol. The esterification process was carried out at 60oC and varied with independent variables, namely catalyst loading (5-10%-b), time (2-4 hours), and molar ratio (1:6-1:12). The experimental design was determined using the Response Surface Method (RSM) using Design Expert. From the study results, the best variation obtained was a conversion of 87.03% with a variation of catalyst loading of 7.5%-b, a time of 4 hours, and a molar ratio of 1:12.